Argon 1s−2 Auger hypersatellites. (30th December 2020) - Püttner, Ralph; Li, Yongjun; Zeng, Jiaolong; Koulentianos, Dimitris; Marchenko, Tatiana; Guillemin, Renaud; Journel, Loïc; Travnikova, Oksana; Zmerli, Moustafa; Céolin, Denis; Azuma, Yoshiro; Kosugi, Satoshi; et al.
Abstract: The 1 s −2 Auger hypersatellite spectrum of argon is studied experimentally and theoretically. In total, three transitions to the final states 1 s −1 2 p −2 ( 2 S e, 2 D e ) and 1 s −1 2 s −1 ( 1 S )2 p −1 ( 2 P o ) are experimentally observed. The lifetime broadening of the 1 s −2 → 1 s −1 2 p −2 ( 2 S e, 2 D e ) states is determined to be 2.1(4) eV. For the used photon energy of hν = 7500 eV a KK / K ionisation ratio of 2.5(3) × 10 −4 is derived. Generally, a good agreement between the experimental and present theoretical energy positions, linewidths, and intensities is obtained.